Psychological distress among Malaysian University students: the protective roles of hope, optimism, resilience, and self-efficacy - Wu, Shin Ling *; Mah, Pei Nee; Yap, Chin Choo *; Fam, Jia Yuin * (Taylor & Francis, 2025)
Psychological distress is a growing concern among university students, yet the role of Psychological Capital (PsyCap) components in mitigating distress remains unclear. This study examines the protective roles of self-efficacy, optimism, hope, and resilience on psychological distress among Malaysian university students. A total of 547 students aged 18 to 24years (M=21.23, SD = 1.82) participated in this cross-sectional correlational study. Using SmartPLS software, the regression analysis showed that self-efficacy and optimism were significant negative predictors of psychological distress, whereas pessimism and succumbing were significant positive predictors. However, hope and resilience did not exhibit significant predictive effects. These findings highlight the protective roles of self-efficacy and optimism in reducing distress, while acknowledging the detrimental impact of pessimism and succumbing. Outcomes of the study support Psychological Distress Theory and partially validate PsyCap, highlighting the distinct contributions of its components on psychological distress. Addressing these negative psychological constructs through targeted interventions such as self-efficacy enhancement workshops and cognitive-behavioural programs may help reduce pessimistic thoughts and psychological distress among university students.